CONTROL OF AGRICULTURAL MOBILE UNITS WITH USE OF THE GLONASS/GPS NAVIGATION SYSTEM - A. Yu. Izmaylov; V. K. Khoroshenkov; E. S. Luzhnova (Сельскохозяйственные машины и технологии)
Agricultural machine and tractor units operate in the conditions of the variable action caused by the numerous disturbance having casual character. In this regard optimization of unit operating modes at disturbance stochastic nature is necessary. The problems of control of the agricultural unit (AU) solved by means of electronics subtending existence of universal system of receiving and use of information display. It was showed that at processes control automation proceeding at AU operation the following problems are solved: regulation of position of working tools of mounted and trailing machines, norms and uniformity of agricultural materials application into the soil on width of capture and depth depending on movement speed; automation of power transmission of AU; regulation of engine load; control of technological, power and operational parameters, including automation of MTA driving. The modern AU control system was synthesized. Several program levels were allocated in structure of AU control and management. It was showed that at the first level direct control of the unit in really measured parameters is exercised. The second level connects operations of control of the operated systems. Optimization procedures belong to the third level. Driving is one of the important parameters connected with unit operation. Established that at the mobile unit movement it is influenced by the casual disturbance of the fundamental (with the period of 100-200 m, with an amplitude of 5 m) and phase (the period of 17-30 m and amplitude - 0,1 m) oscillations resulting from variation of specific soil drag, width of capture and cultivation depth. It was proved that at creation of automatic control systems of it is necessary to consider casual character and ergonomics of disturbance.